2019
DOI: 10.32391/ajtes.v3i2.48
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Study of Surgical Repair of Gunshot Injuries of Peripheral Nerves.

Abstract: Background: Shotgun injuries of the peripheral nerves are presented frequently during the last decades at the Service of Neurosurgery of UHC “Mother Theresa” in Tirana. In such cases the surgical repair of brachial plexus and peripheral nerves constitutes a challenge with relation to difficulties related with mechanism of injury, coexistence of other vascular damage, bone, soft tissue and visceral lesions. Materials and methods: A retrospective study of operated cases with shotgun injuries treated in our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…[4] In a 68-case retrospective study by Alimehmeti et al on the surgical repair of GSW PNIs ranging from interfascicular neurolysis to direct end-to-end microsuture, they determined that early surgical repair of GSW PNIs resulted in improved pain relief and sensory motor improvements. [1] Another study by Pannell et al focused on patients with clinical palsy after GSW to the upper extremity and found that due to the high incidence of traumatic nerve laceration, which requires surgical repair after a GSW, it is best to perform early nerve exploration in these patients. [6] In addition, the risk of patients progressing to narcotic dependence for pain management may be reduced through timely intervention.…”
Section: Intervention (2 Months After Gsw)mentioning
confidence: 99%
“…[4] In a 68-case retrospective study by Alimehmeti et al on the surgical repair of GSW PNIs ranging from interfascicular neurolysis to direct end-to-end microsuture, they determined that early surgical repair of GSW PNIs resulted in improved pain relief and sensory motor improvements. [1] Another study by Pannell et al focused on patients with clinical palsy after GSW to the upper extremity and found that due to the high incidence of traumatic nerve laceration, which requires surgical repair after a GSW, it is best to perform early nerve exploration in these patients. [6] In addition, the risk of patients progressing to narcotic dependence for pain management may be reduced through timely intervention.…”
Section: Intervention (2 Months After Gsw)mentioning
confidence: 99%
“…Primary repair of these injuries is contraindicated because it is impossible to determine the exact proximal and distal extent of nerve injury. Recent research suggests that early surgical repair, though, appears to have superior results compared to repair several months after nerve injury in terms of pain treatment and in improving motoric and sensitivity, [33] with consensus for repair being set within 6 months, after injury [32]. Long term follow-up is of utmost importance in order to evaluate the need for further surgical procedures, for example in case of distal decompressive surgery in anatomical tunnels [33].…”
Section: Nerve Reconstructionmentioning
confidence: 99%